2019
DOI: 10.1016/j.ajodo.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

A needle in a haystack: Report of a retained archwire fragment in the pterygomandibular space

Abstract: This clinical report describes a retained archwire fragment, discovered during a new-patient examination of a young woman seeking orthodontic retreatment. The diagnostic process, care coordination, and patient management decisions are discussed, along with a brief exploration of clinical considerations associated with this incident. A suggested emergency prevention and response protocol is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…During the epidemic period of the COVID-19, it is recommended to manage only orthodontic emergencies to prevent further harm, such as brackets debonding, archwire or ligature wire deformation or shifting, oral mucosa irritations, and anchorage implants loosening. [37][38][39] Nevertheless, orthodontists or assistants should evaluate the emergencies before allowing the patients to come to the office by requesting photographs or videos from the patients. If the emergency could be managed at home by remote instructions to the patients over the phone or other communication tools, such as WeChat (Tencent, Shenzhen, China) and WhatsApp (Menlo Park, Calif), it is unnecessary for them to come to the office.…”
Section: Infection Controls During Orthodontic Proceduresmentioning
confidence: 99%
“…During the epidemic period of the COVID-19, it is recommended to manage only orthodontic emergencies to prevent further harm, such as brackets debonding, archwire or ligature wire deformation or shifting, oral mucosa irritations, and anchorage implants loosening. [37][38][39] Nevertheless, orthodontists or assistants should evaluate the emergencies before allowing the patients to come to the office by requesting photographs or videos from the patients. If the emergency could be managed at home by remote instructions to the patients over the phone or other communication tools, such as WeChat (Tencent, Shenzhen, China) and WhatsApp (Menlo Park, Calif), it is unnecessary for them to come to the office.…”
Section: Infection Controls During Orthodontic Proceduresmentioning
confidence: 99%
“…9 Bradford et al reported a very similar case of retained arch wire fragment in the pterygomandibular space discovered as an incidental radiographic finding. 10 In the present case, retrieval of the object was taxing for the surgeon, and irritation and damage of tissues during the effort taken were extremely stressful to the patient as well. Hence, prevention is the best approach in our increasingly litigious world as foreign body impaction can not only cause physical and emotional distress to the patient but can ruin the reputation of dental practitioners as well.…”
Section: Discussionmentioning
confidence: 66%
“…Migration of foreign bodies like staples and fish bones within oral and cervical space has been reported in literature previously 9 . Bradford et al reported a very similar case of retained arch wire fragment in the pterygomandibular space discovered as an incidental radiographic finding 10 …”
Section: Discussionmentioning
confidence: 91%
“…1 The only problem with this has been that when regular monitoring of orthodontic treatment cannot be done, there is every scope for a minor issue escalating into a dental emergency. 2-6…”
Section: Introductionmentioning
confidence: 99%
“…1 The only problem with this has been that when regular monitoring of orthodontic treatment cannot be done, there is every scope for a minor issue escalating into a dental emergency. [2][3][4][5][6] With community transmission slowly ebbing in most parts of the world, decisions are being made to revert back to a pattern of normalcy while attempting to strike a balance between lives and livelihoods as the danger has not completely passed us yet. 7 This article strives to re-emphasize infection control protocol that can allow for safe practicing even under challenging circumstances to prevent recurrences or relapses of disease transmission.…”
Section: Introductionmentioning
confidence: 99%